2019
DOI: 10.3390/nano9050705
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of Poly (dimethylsiloxane) Membranes by Incorporating SiO2 Microspheres Generated Silver Nanoparticles

Abstract: The nonspecific adsorption of proteins and bacteria on the surface of polydimethylsiloxane (PDMS) had been a serious concern in a wide range of applications, such as medical devices. In order to improve the anti-adhesive and antibacterial capability, bare silver nanoparticles (AgNPs, ~15 nm) were generated in-situ on their surface without extra reducing and stabilizing agents. The main reason for this was that the SiO2 microspheres that are covalent bonded to the bulked PDMS could not only generate AgNPs spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Over the past decades, click chemistry reactions presented profound clinical applications of which the in-situ synthesis of enzyme inhibitors presents the most recent development [125], which also validates considerable biocompatibility of these reactions for designing bio-conjugated nanopharmaceuticals. However, the azide-alkyne click cycloaddition approach for developing bioconjugated AgNPs generally requires a tedious pre-synthesis of azide/ alkyne functionalized participating species [126]. In addition, this approach often suffers a low yield, thereby limiting its efficacy for nanoparticle bio-conjugation [127].…”
Section: Azide-alkyne Click Chemistry For Agnps Bio-conjugationmentioning
confidence: 99%
“…Over the past decades, click chemistry reactions presented profound clinical applications of which the in-situ synthesis of enzyme inhibitors presents the most recent development [125], which also validates considerable biocompatibility of these reactions for designing bio-conjugated nanopharmaceuticals. However, the azide-alkyne click cycloaddition approach for developing bioconjugated AgNPs generally requires a tedious pre-synthesis of azide/ alkyne functionalized participating species [126]. In addition, this approach often suffers a low yield, thereby limiting its efficacy for nanoparticle bio-conjugation [127].…”
Section: Azide-alkyne Click Chemistry For Agnps Bio-conjugationmentioning
confidence: 99%
“… 28 To this end, silver is a well-studied material for creating antibacterial surfaces by a variety of methods, including physical deposition and chemical reduction; however, in most of these methods, silver particles are weakly bound to the surface and easily leach out in the solution, body fluids, and tissues. To circumvent this, Shen and associates 29 produced an anti-adhesive coating incorporating antibacterial material by covalently bonding specially designed silica microspheres with polydimethylsiloxane. Bare silver nanoparticles are spontaneously generated on the surface of these silica microspheres through the reduction process of silver ions by thiol groups.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that such a surface treatment inhibited the growth of Escherichia coli and Bacillus subtilis . 29 However, the procedure reported is a multistep, time-consuming process; therefore, the quest to find an antibiofilm coating continues.…”
Section: Introductionmentioning
confidence: 99%
“…155 Specifically, in the manufacturing of UTI devices, PDMS is usually applied due to its great biocompatibility, excellent chemical stability, and mechanical resistance. 156,157 However, the use of PDMS in the biomedical sector carries some drawbacks, such as it is vulnerable to non-specific surface attachment of pathogens and protein. Currently, various studies reported the enhancement of antibiofouling characteristics of PDMS by the attachment of MWCNTs.…”
Section: Application Of Cnts In Urinary Tract Devicesmentioning
confidence: 99%